Does Financial and Trade Liberalization Drive Private Savings in Pakistan? - Hye, Qazi Muhammad Adnan; Lau, Wee-Yeap (Asian Development Policy Review, 2018)
This study contributes to the empirical literature by estimating the impact of financial and trade liberalization on private savings in the case of Pakistan. The ARDL approach to cointegration is used to provide empirical evidence of relationship among financial liberalization, trade liberalization, and private savings. The results indicate that the private income, deposit rate (also known as savings rate), financial system liberalization and public savings have a positive impact on private savings. On the other hand, old age dependency, capital account liberalization, and financial openness are negatively associated with private savings. The trade liberalization index is found to be negatively associated with private savings albeit not significant. An important policy suggestion emerging from the results is that it is vital for the government to liberalize the financial system, i.e. bank sector and stock market in order to mobilize the private savings. Practical implications: The private savings should be mobilized as means to create microfinance for individuals and households. Social implications: Social welfare will increase if microfinance can provide a means to poorer households to start small businesses. To the best the authors’ knowledge, this study is the first of its kind to use recent indicators of trade and financial liberalization developed by Lane and Milesi-Ferretti (2007), Wacziarg and Welch (2008) and Chinn and Ito (2006) in the case of Pakistan.